Comportamento de duas misturas de seis variedades de feijão (Phaseolus vulgaris L) - Américo Cardoso, Antônio; Vieira , Clibas (Revista Ceres, 2025)
The behavior of two mixtures of six varieties of dry beans (Phaseolus vulgaris) was studied in Viçosa, Minas Gerais. Both mixtures were formulated with equal numbers of seeds of each variety and both had in common the varieties ‘Rico 23’ and 37-R.